Tax Knowledge and Gender: The Impact in Improving Tax Compliance of MSME Actors - Mei Rani Amalia; Agnes Dwita Susilawati; Yuniarti Herwinarni (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2023)
The objective of the Directorate General of Taxes, a governmental entity operating within the Ministry of Finance, is to enhance tax revenue by implementing tax reforms that streamline the tax system. These reforms encompass modifications to tax rates, non-taxable income thresholds, and tax collection procedures. Despite serving as a fundamental pillar of the nation's economy, a significant number of Micro, Small, and Medium Enterprises (MSMEs) exhibit non-compliance concerning their tax obligations. A research investigation was undertaken to ascertain the influence of tax knowledge, gender, and individual characteristics on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs) in the tax office of KPP Pratama Kota Tegal. The employed metadata analysis methodology involved utilizinutilizationar regression analysis. The intended outcome of this research endeavor is the endeavor of the findings in reputable journals that are accredited with a SINTA rating of 3 or 4. The primary objective of this research is to enhance tax compliance among Micro, Small, and Medium Enterprises (MSMEs), hence leading to an increase in regional revenues. Additionally, this study seeks to contribute to overall development efforts.